Implementasi Pasal 35 Peraturan Pemerintah Nomor 43 Tahun 2004 tentang Bantuan Sosial Lanjut Usia: Perspektif Siyasah Tanfidziyah - Salsa Bila Azzahra (Jurnal Hukum Lex Generalis, 2026)
Social assistance for the elderly is a government social protection policy aimed at ensuring the welfare of vulnerable groups, as mandated by Article 35 of Government Regulation Number 43 of 2004. This research analyzes the implementation of these provisions at the Social Affairs Office of Bandar Lampung City through the perspective of siyasah tanfidziyah. The method employed is qualitative, utilizing interviews and documentation. The findings indicate that the implementation of social assistance for the elderly has not been optimal due to budget constraints and inaccuracies in recipient data, resulting in aid distribution that is not fully targeted. This condition potentially leads to legal implications, such as the unfulfillment of the elderly's welfare rights and the possibility of maladministration in data collection and distribution. Nevertheless, clear regulations, the role of social assistants and internal supervision serve as supporting factors for the program. In the siyasah tanfidziyah perspective, this policy reflects the government's responsibility in realizing maslahah (public interest), yet it requires governance improvements through data updates and budget increases to ensure greater effectiveness and accuracy.